O gerenciamento por processos na administração pública: o caso da UFSCar - Paula, Vérica Marconi Freitas de (2008)
The focus on management practices - especially the ones that improve the fulfillment of the demands and needs of people involved with the organization - has grown due to the increase in competition, causing changes in the organizations conventional way of working. In the public sector, management has been modified and still is. Literature shows that the present model of Public Management does not fulfill completely the needs and growing demands of the citizens. As a consequence, it is possible to find some areas in which managerial practices have already been adopted. Therefore, this study analyses the viability of applying the strategy of management by processes in Public Management. This strategy has been applied to private companies with strong positive results. The empirical part of the study was developed at UFSCar (Federal University of São Carlos), aiming at identifying the present context and the main aspects (favorable or not) involved in introducing the strategy of management by processes in four selected processes.